Research Progress on Mono-ADP-Ribosyltransferases in Human Cell Biology - Gan, Yujie; Sha, Huanhuan; Zou, Renrui; Xu, Miao; Zhang, Yuan; Feng, Jifeng; Wu, Jianzhong (Frontiers in Cell and Developmental Biology, 2022)
ADP-ribosylation is a well-established post-translational modification that is inherently connected to diverse processes including DNA repair, transcription, and cell signaling. The crucial roles of mono-ADP-ribosyltransferases (mono-ARTs) in biological processes have been identified in recent years by the comprehensive use of genetic engineering, chemical genetics, and proteomics. This review provides an update on current methodological advances in the study of these modifiers. Furthermore, the review provides details on the function of mono ADP-ribosylation. Several mono-ARTs have been implicated in the development of cancer, and this review discusses the role and therapeutic potential of some mono-ARTs in cancer.